Effect of Quality of Health Care on Outpatients’ Satisfaction (A Study from Laboratory of Ba’a General Hospital, Rote Ndao, East Nusa Tenggara, Indonesia, Year 2022) - Tamonob, Melinda; Kenjam, Yoseph; Sirait, Rina Waty (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Quality of service is one of the elements that can affect patient satisfaction in the laboratory. Ba'a Rote District hospital, is the only hospital in Rote Ndao District which has a laboratory unit to support efforts to diagnose disease and restore health. Measurement of patient satisfaction can be used as a tool for evaluating the quality of health services. This study aims to determine the effect of the quality of health services on the level of satisfaction of outpatients in the Ba'a Rote Hospital laboratory in 2022.Subjects and Method: A cross-sectional study was conducted at the Rote Ndao Hospital Laboratory, East Nusa Tenggara, Indonesia, from February to September 2022. A total of 85 subjects were selected for this study. The dependent variable is satisfaction. The independent variable is the tangible dimension, the empathy dimension, the reliability dimension, responsiveness and assurance. The data were collected using a questionnaire, and analyzed using a logistic regression test.Results: Reliability dimension (aOR= 5.30; 95% CI= 1.90 to 13.30; p= 0.001), responsiveness dimension (aOR= 6.49; 95% CI=2.37 to 17.77; p<0.001), assurance dimension (aOR= 33.58; 95% CI = 8.70 to 129.57; p< 0.001), empathy dimension (aOR= 12.53; 95% CI=4.37 to 35.94; p<0.001), and tangibles dimension (aOR= 9.25; 95% CI=3.31 to 25.84; p<0.001) significantly influence patient satisfaction.Conclusion: The tangible dimension, the empathy dimension, the reliability dimension, the responsiveness dimension, the assurance dimension influence patient satisfaction. Keywords: service quality, patient satisfaction, hospital, laboratoryCorrespondence:Melinda Tamonob. Masters Program in Public Health, Faculty of Public Health, Universitas Nusa Cendana. Jl. Lasiana, Klp. Lima, Kupang, East Nusa Tenggara, Indonesia. Email: linda456tamonob@gmail.com. Mobile: +62 822-5136-3311.Journal of Health Policy and Management (2023)https://doi.org/10.26911/thejhpm.2023.08.02.01